Urbanistične delavnice: orodje v prostorskem planiranju - Ažman Momirski, Lučka (Urbani izziv, 1997)
The article deals with urban design workshop and a competition, co-financed by the Ministry for Environment and Physical Planning in 1996. The focus of the article is on identifying urban design workshops as promoters for participation of businesses and the general public in planning processes and town management. At first, the general goals of workshops are presented, such as: a mode for participation, negotaiation, control over procedures and possible presentation of results. An important aspect is work with students. In continuation, the goals, proceedings and results of lastyears urban design workshops are discussed. The work shop in Izola is presented in detail. Findings on the preparation and completion of urban design workshops in Slovenia concludes the article.
Keywords: Izola; prostorsko planiranje; spatial planning; urbanism; urbanistično planiranje; urbanizem